Enjeux et limites de la création lectorale - Alain Trouvé (Carnets)
This paper aims at showing under what conditions the reader can, in reading a writer’s text, invent a new meaning which escapes the latter’s intention. It is the writer’s implication as total subject, intertwined conscious and subconscious, which produces the “syncope of meaning” leading to any authentic creative act. Violating the letter of an author’s text to impose another by twisting the theory of a ghost text for the occasion simply amounts to erasing the specificity of the literary text, which lies in the gap between immediately visible meaning and other potential or hidden strata of meaning, and to ruining the possibility of creative interpretation. Putting the roles of author and reader back into perspective does not mean negating the latter’s creativity ; on the contrary, it amounts to giving him the opportunity to show the extent of his talent.